Effectiveness of Breast and Eye Shielding During Cervical Spine Radiography: An Experimental Study - Elshami W; Abuzaid MM; Tekin HO (Dove Medical Press, 2020)
Wiam Elshami, Mohamed M Abuzaid, H O Tekin Medical Diagnostic Imaging Department, College of Health Sciences, University of Sharjah, Sharjah, United Arab EmiratesCorrespondence: Wiam Elshami Email welshami@sharjah.ac.aePurpose: This study assessed the effectiveness of breast and eye shielding and measured the radiation dose to radiosensitive tissues (eyes and breasts) due to scatter radiation during cervical spine X-ray radiography examinations.Methods: Using an anthropomorphic phantom, the scattered radiation dose was measured before and after the placement of the lead shield over the eyes and breasts in the anteroposterior (AP) and left lateral projection. A regression formula was utilized to determine the exposure. Mean values and standard deviation of breasts and eyes doses were calculated. The paired two sample t-test was used to compare the recorded dose before and after shielding placement.Results: Radiation shielding of eyes and breasts during AP cervical spine X-ray decreased radiation dose to the breasts by 99.9% and to the left and right eye by 91% and 89%, respectively. For the left lateral cervical spine X-ray, the radiation dose decreased by 26% and 31% for the left and right eye, respectively, and by 23% and 99% for the left and right breast, respectively. A significant difference was noted comparing the dose before and after the implementing shielding on the eye and breast.Conclusion: According to the results presented, the dose is significantly reduced, especially considering that they are not in the area of interest but are exposed to scatter radiation.Keywords: radiation exposure, radiation dose, radiation protection, ALARA, radiography